Learning styles among nursing students, the implications for higher education institutions: A systematic review - Frantz, J (South African Journal of Higher Education, 2016)
Understanding learning styles of nursing students has been highlighted as an area in the scholarship of teaching that needs attention. The aim of this review was to determine the common learning styles of nursing students and determine the appropriate teaching styles needed. A search was conducted using various databases and journals for the periods from 2000 to 2013. Two reviewers independently evaluated the methodological quality of the studies reviewed. The results are presented in a narrative. The 11 articles included in the review. represented four continents and were primarily descriptive studies. The review highlighted that nursing students preferred the kineasthetic and multi-modal learning styles. Kinesthetic learners prefer live examples and lots of interaction. Interactive and real life experiences as teaching methodologies are preferred methods by nursing students and is seen as a holistic approach that incorporated all of their senses of seeing, feeling, smelling, hearing and sometimes tasting.